A STUDY OF TEACHERS’ LEARNING AGILITY IN UPPER CENTRAL PROVINCIAL ANUBAN SCHOOLS - Mangmool, Pakwan; Chaemchoy, Sukanya (Journal of Educational Review Faculty of Education in MCU, 2024)
The objective of this research article was to study the level of teachers’ learning agility in upper central provincial Anuban Schools by using the learning agility conceptual framework. The research adopted a descriptive research method. The population was upper central provincial Anuban Schools. The informants of the research are 234 teachers selected from 597 teachers in 7 upper central provincial Anuban Schools by using simple random sampling. The research tool was a questionnaire regarding the level of teachers’ learning agility in upper central provincial Anuban Schools. The data were analyzed by statistical analysis methods such as frequency, percentage, mean, and standard deviation. The research findings revealed that the overall level of teachers’ learning agility in upper central provincial Anuban Schools was in a moderate level. When considering each aspect of the level of teachers’ learning agility in upper central provincial Anuban Schools, it was found that self-awareness was at the highest level, followed by people agility, result agility and mental agility respectively. Meanwhile, change agility was at the lowest level.